Function of the ETS transcription factor Yan in border cell migration. - Schober, M.; Rebay, I.; Perrimon, N. (Development, 2005)
Invasive cell migration in both normal development and metastatic cancer is regulated by various signaling pathways, transcription factors and cell-adhesion molecules. The coordination between these activities in the context of cell migration is poorly understood. During Drosophila oogenesis, a small group of cells called border cells exit the follicular epithelium to perform a stereotypic, invasive migration. We find that the ETS transcription factor Yan is required for border cell migration and that Yan expression is spatiotemporally regulated as border cells migrate from the anterior pole of the egg chamber towards the nurse cell-oocyte boundary. Yan expression is dependent on inputs from the JAK/STAT, Notch and Receptor Tyrosine Kinase pathways in border cells. Mechanistically, Yan functions to modulate the turnover of DE-Cadherin-dependent adhesive complexes to facilitate border cell migration. Our results suggest that Yan acts as a pivotal link between signal transduction, cell adhesion and invasive cell migration in Drosophila border cells.